Accessing the archive: A TV history of Afrikaans film. (1st April 2015) - Tomaselli, Keyan
This article explores the political economy of the Afrikaans film production industry. The point of entry is a TV documentary series, Far Away in the Movies (Lategan, 2011). A basic methodology for examining visualization of media history is developed by examining the series as a point of reference. The issue of film archives and challenges of obtaining access is discussed. Issues of memory and how interviewees and scholars remember is conducted through autoethnographic analysis.